2018
DOI: 10.1155/2018/8781721
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Polycythemia of Undetermined Etiology and Smouldering Plasma Cell Myeloma

Abstract: The combination of polycythemia and plasma cell myeloma occurring concurrently is very rare and few cases have been reported in the literature. Further, the vast majority of these cases are cases of polycythemia vera and myeloma. Here, we present a case of polycythemia of undetermined etiology and myeloma. The patient is a 48-year-old Caucasian male who was originally diagnosed with polycythemia of undetermined etiology. Twelve years later, when a bone marrow biopsy was performed in an attempt to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Patients with co‐existing PCD and either Ph‐positive CML (Nitta et al , ) or Ph‐negative MPN have been reported (Economopoulos et al , ; Fink et al , ; Kuroda et al , ; Malhotra et al , ; Le Clech et al , ; Marchetti et al , ; Katerji & Hudson, ; Bouchla et al , ), and it has been described that the presence of monoclonal protein at diagnosis of MPN is associated with worse prognosis (Le Clech et al , ). However, in these studies the presence of JAK2V617F in plasma cells has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with co‐existing PCD and either Ph‐positive CML (Nitta et al , ) or Ph‐negative MPN have been reported (Economopoulos et al , ; Fink et al , ; Kuroda et al , ; Malhotra et al , ; Le Clech et al , ; Marchetti et al , ; Katerji & Hudson, ; Bouchla et al , ), and it has been described that the presence of monoclonal protein at diagnosis of MPN is associated with worse prognosis (Le Clech et al , ). However, in these studies the presence of JAK2V617F in plasma cells has not been described.…”
Section: Introductionmentioning
confidence: 99%